Alumni associations in Kazakhstan: Building the future of higher education institutions through its graduates - Sagitova, Roza (Nazarbayev University Graduate School of Education, 2018)
As HEIs are becoming autonomous, the sheer need to search for new ways to overcome financial difficulties and diversify the sources of revenue becomes a necessity, not just a choice. The research problem, therefore, is underpinned by the need for higher education institutions to adapt new approaches to income-generating projects, allowing to conduct an investigation of the topic of alumni associations for them historically to serve as one of the fund-raising and networking venture at the universities of the US and Europe...
Keywords: alumni associations in Kazakhstan; higher education institutions